High-voltage polymer electrolyte and application thereof in energy storage equipment
By copolymerizing alkyl acrylates, fluoro-containing acrylates and polyethylene glycol diacrylic acid, high-voltage resistant polymer electrolytes are constructed, solving the problem of decomposition or reaction of polymer electrolytes at high voltages, and improving the electrochemical stability and electrochemical window.
Patent Information
- Application Number
- CN202411897218.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
AI Technical Summary
Existing polymer electrolytes are prone to decomposition or reaction at high voltages, resulting in poor electrochemical stability and narrow electrochemical window, making it difficult to broaden the electrochemical window on the basis of ensuring the advantages of polymer electrolytes.
By copolymerizing alkyl acrylates, fluoro-containing acrylates and polyethylene glycol diacrylic acid, a high-pressure resistant polymer electrolyte is constructed, the cross-linking network of electrolytes is optimized, and the electrochemical stability and electrochemical window are improved.
The electrochemical stability and electrochemical window of high-voltage polymer electrolytes are significantly improved, the ionic conductivity and mechanical strength are enhanced, and the cell cycle performance and rate performance are optimized.
Smart Images

Figure CN119650837A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical energy storage, and in particular relates to a high-voltage polymer electrolyte and its application in energy storage equipment. Background Art
[0002] As the best energy storage device, lithium-ion batteries have been widely used in our daily life and production. However, due to the flammability and explosiveness of liquid electrolytes, liquid lithium batteries currently on the market are not only difficult to achieve the ideal high energy density, but also bring serious safety hazards. Therefore, the use of inorganic solid electrolytes and polymer electrolytes to replace liquid electrolytes has become the focus of current research.
[0003] Compared with inorganic solid electrolytes, polymer electrolytes can achieve excellent electrode / electrolyte interface contact when used in batteries due to their good flexibility and easy processing. At the same time, due to their excellent mechanical properties and low density, they can effectively improve the performance and safety of batteries when used as electrolytes. However, the interface interaction between polymer electrolytes and electrodes is complex, and they are prone to decomposition or reaction under high voltages, which leads to the fact that polymer electrolytes often have a narrow electrochemical window at room temperature and poor electrochemical stability. Currently, common solutions include introducing fillers or ionic liquids, or adding coatings to the surface of polymer electrolytes. Although these methods can optimize the electrochemical stability of polymer electrolytes to a certain extent and improve the electrochemical window, they often require sacrificing some of the advantages of the polymer electrolytes themselves. It is a major difficulty in current research to broaden the electrochemical window of polymer electrolytes at room temperature and improve the electrochemical stability while ensuring the advantages of the polymer electrolytes themselves. Summary of the invention
[0004] In order to solve the problems of the prior art, the present invention provides a high-voltage polymer electrolyte. A high-voltage polymer electrolyte is constructed by copolymerizing alkyl acrylate, fluorine-containing acrylate and polyethylene glycol diacrylate. While ensuring good processing and flexibility of the polymer, the electrochemical stability of the high-voltage polymer electrolyte is improved and the electrochemical window is widened.
[0005] In a first aspect, the present invention provides a high-voltage polymer electrolyte, wherein the precursor solution includes an alkyl acrylate with a molecular weight of 80 to 150 g / mol, polyethylene glycol diacrylate with a weight average molecular weight of 400 to 1000 g / mol, a fluorine-containing acrylate with a molecular weight of 200 to 400 g / mol, a lithium salt, a solvent, and an initiator;
[0006] The structural formula of alkyl acrylate is The structural formula of fluorinated acrylate is
[0007]
[0008] Wherein, R1 and R3 are selected from one of H and methyl, R2 is selected from one of C1 to C5 alkyl groups, and R4 is selected from a fluorine-substituted phenyl group or a C3-C7 alkyl group substituted with at least 4 fluorine groups.
[0009] As some preferred schemes, the raw materials of the high-voltage polymer electrolyte include alkyl acrylate with a molecular weight of 100-120 g / mol, polyethylene glycol diacrylate with a weight average molecular weight of 400-600 g / mol, fluorine-containing acrylate with a molecular weight of 225-350 g / mol, lithium salt, solvent, and initiator, wherein R1 is selected from methyl, R2 is selected from C1-C3 alkyl, R3 is selected from methyl, and R4 is selected from C3-C5 alkyl substituted with at least 4-12 fluorines.
[0010] As some exemplary schemes, the alkyl acrylate can be selected from one or more of methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, propyl acrylate, isopropyl acrylate, propyl methacrylate, butyl acrylate, isobutyl acrylate, butyl methacrylate, amyl acrylate, isoamyl acrylate, and amyl methacrylate.
[0011] As some exemplary schemes, the polyethylene glycol diacrylate can be selected from one or more polyethylene glycol diacrylates having a weight average molecular weight of 400 g / mol, 575 g / mol, 600 g / mol, 700 g / mol, and 1000 g / mol.
[0012] As some exemplary schemes, the fluorine-containing acrylates include one or more of hexafluorobutyl acrylate, 1H,1H-perfluoropropyl methacrylate, 2,2,3,3,4,4,4-heptafluoro-butyl methacrylate, 1H,1H,7H-dodecyl methacrylate, 2-(perfluorobutyl)ethyl acrylate, dodecafluoroheptyl methacrylate, octafluoropentyl acrylate, 2-(perfluorobutyl)ethyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, hexafluorobutyl methacrylate, hexafluoroisopropyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, octafluoropentyl methacrylate, pentafluorophenyl methacrylate, and hexafluorobutyl acrylate.
[0013] As a further solution, the mass content of the alkyl acrylate in the high-voltage polymer electrolyte raw material is selected from 0.1%-5%.
[0014] As a further solution, the mass content of the alkyl acrylate in the high-voltage polymer electrolyte raw material is selected from 1%-3%.
[0015] As a further solution, the mass content of the polyethylene glycol diacrylate in the high-voltage polymer electrolyte raw material is selected from 2% to 5%.
[0016] As a further solution, the mass content of the polyethylene glycol diacrylate in the high-voltage polymer electrolyte raw material is selected from 2% to 4%.
[0017] As a further solution, the mass content of the fluorine-containing acrylate in the high-voltage polymer electrolyte raw material is selected from 5% to 8%.
[0018] As a further solution, the mass content of the fluorine-containing acrylate in the high-voltage polymer electrolyte raw material is selected from 5% to 7%.
[0019] As a further solution, the mass content of the solvent in the high-voltage polymer electrolyte raw material is selected from 40% to 95%.
[0020] As a further embodiment, the solvent is selected from carbonate solvents and carboxylate solvents.
[0021] As a further solution, the carbonate solvent is selected from a mixture of one or more of cyclic carbonates and linear carbonates.
[0022] As a further solution, the carboxylate solvent is selected from one or a mixture of acetate solvents, propionate solvents, and butyrate solvents.
[0023] As a further solution, the high-voltage polymer electrolyte may further include a fluorine-containing co-solvent.
[0024] As a further solution, the lithium salt is selected from any one or more of organic lithium salts and inorganic lithium salts.
[0025] As a further solution, the organic lithium salt is selected from any one or more of lithium sulfonate salts, lithium oxalate salts and lithium borate salts.
[0026] As a further solution, the inorganic lithium salt is selected from any one or more of inorganic lithium borate salts, inorganic lithium phosphate salts, and inorganic lithium chlorate salts.
[0027] As a further embodiment, the concentration of the lithium salt in the solvent is selected from 2-4M.
[0028] As a further embodiment, the fluorine-containing co-solvent is selected from one or more of fluoroethers, fluorobenzenes, fluoroesters, and fluorosilicone ethers.
[0029] As a further solution, the mass content of the fluorine-containing co-solvent in the high-voltage polymer electrolyte raw material is selected from 0 to 50%.
[0030] As a further solution, the mass of the initiator is 2% of the sum of the masses of alkyl acrylate, polyethylene glycol diacrylate and fluorine-containing acrylate.
[0031] In a second aspect, the present invention further provides an energy storage device, which uses the high-voltage polymer electrolyte provided by the present invention as an electrolyte.
[0032] As a further solution, the energy storage device includes a lithium-ion battery.
[0033] As a further solution, the lithium-ion battery also includes a positive electrode sheet, a negative electrode sheet, and a separator.
[0034] As a further solution, the positive electrode sheet includes a positive electrode material layer and a positive electrode current collector.
[0035] As a further solution, the positive electrode material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductor.
[0036] As a further solution, the positive electrode binder is selected from at least one of thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose and styrene butadiene rubber.
[0037] As a further embodiment, the positive electrode conductor includes a crystalline carbon material and an amorphous carbon material.
[0038] As a further solution, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer.
[0039] As a further solution, there is no restriction on the type of the negative electrode current collector, and technicians can select the corresponding negative electrode current collector according to their needs.
[0040] As a further solution, the negative electrode material layer includes a negative electrode active material, a negative electrode binder and a negative electrode conductor.
[0041] As a further solution, the type of the diaphragm is not limited, and technicians can choose according to their needs.
[0042] In a third aspect, the present invention also provides a method for preparing a lithium-ion battery, the steps of which are as follows:
[0043] S1: uniformly mixing a lithium salt, a solvent, a fluorinated co-solvent, an alkyl acrylate, polyethylene glycol diacrylate and a fluorinated acrylate, then adding an initiator and mixing uniformly to obtain a polymer electrolyte precursor solution;
[0044] S2: Inject the polymer electrolyte precursor solution into the battery and heat and solidify it to obtain a lithium-ion battery.
[0045] As a further solution, the curing temperature in step S2 is selected from 50°C-80°C.
[0046] As a further solution, the curing time in step S2 is selected from 7h-10h.
[0047] As a further solution, the standing time after the battery assembly is completed in step S2 is selected from 5h-8h.
[0048] As a further solution, the steps of preparing a lithium ion battery are:
[0049] S1: mixing a lithium salt, a solvent, and a fluorinated co-solvent to obtain a solution A, and mixing an alkyl acrylate, polyethylene glycol diacrylate, and a fluorinated acrylate to obtain a solution B;
[0050] S2: Mix solution A and solution B, add an initiator, mix well, and obtain a polymer electrolyte precursor solution;
[0051] S3: Inject the polymer electrolyte precursor solution into the battery and heat and solidify it to obtain a lithium-ion battery.
[0052] As a further solution, the steps of assembling the battery are not limited in principle, and technicians can assemble it according to needs. For example, the battery can be assembled in the order of negative electrode shell, negative electrode, injection of precursor solution, separator, injection of precursor solution, positive electrode, gasket, spring clip, and positive electrode shell.
[0053] Compared with the prior art, the present invention has at least the following beneficial effects:
[0054] The present invention significantly improves the comprehensive performance of high-voltage polymer electrolytes through a carefully designed copolymerization strategy. By precisely controlling the molecular weight of alkyl acrylates, fluorinated acrylates, and polyethylene glycol diacrylates, we have achieved enhanced ion conductivity and solvent resistance of the electrolyte, effectively broadening the electrochemical window. This optimization not only improves the ionic conductivity, but also enhances the mechanical strength and ion selectivity of the electrolyte. At the same time, through the introduction of ester groups and fluorine elements, the ionic conductivity is enhanced and a protective LiF-rich SEI film is formed, thereby protecting the electrode and optimizing the battery cycle performance. In addition, the addition of fluorinated co-solvents further optimizes the solvation structure of lithium ions, promotes the participation of anions, provides a more stable ion transport environment for battery operation, and significantly improves the battery's rate performance and cycle stability. Overall, this scheme provides a new type of polymer electrolyte with excellent performance and strong stability for the development of high-voltage battery technology, which is expected to promote the advancement of battery technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0056] Figure 1 It is the electrochemical window diagram of Example 1;
[0057] Figure 2 is the ionic conductivity diagram of Example 1;
[0058] Figure 3 is the coulombic efficiency diagram of lithium metal deposition / stripping of Example 1;
[0059] Figure 4 This is a graph showing the cycle performance of the polymer electrolyte of Example 1 in a LCO||Li battery at 3-4.6V 0.5C;
[0060] Figure 5 This is a rate performance diagram of the polymer electrolyte of Example 1 in a LCO||Li battery at 3 to 4.6 V. DETAILED DESCRIPTION
[0061] For ease of understanding, the present invention will be described in more detail below and examples of the present invention are given, but the scope of the present invention is not limited thereby.
[0062] In a first aspect, the present invention provides a high-voltage polymer electrolyte, wherein the precursor solution includes an alkyl acrylate with a molecular weight of 80 to 150 g / mol, polyethylene glycol diacrylate with a weight average molecular weight of 400 to 1000 g / mol, a fluorine-containing acrylate with a molecular weight of 200 to 400 g / mol, a lithium salt, a solvent, and an initiator;
[0063] The structural formula of alkyl acrylate is The structural formula of fluorinated acrylate is
[0064]
[0065] Wherein, R1 and R3 are selected from one of H and methyl, R2 is selected from one of C1 to C5 alkyl groups, and R4 is selected from a fluorine-substituted phenyl group or a C3-C7 alkyl group substituted with at least 4 fluorine groups.
[0066] This scheme utilizes alkyl acrylate and fluorine-containing acrylate having both C=C structures, and cooperates with polyethylene glycol diacrylate to achieve co-polymerization, and exerts the compounding effect of the three by controlling the molecular weight and weight-average molecular weight of the three, thereby optimizing the polymerization network and giving the high-voltage polymer electrolyte good ion conductivity and solvent resistance, thereby broadening the electrochemical window. Specifically, polyethylene glycol diacrylate, as a flexible cross-linking agent, when its weight-average molecular weight is selected from 400 to 1000 g / mol, helps to form sufficiently spacious lithium ion channels in the polymer network, thereby promoting the effective migration of lithium ions and improving ion conductivity. On this basis, we further introduce alkyl acrylate with a molecular weight of 80 to 150 g / mol. The molecular weight selected from 80 to 150 g / mol enables it to form a tighter cross-linking network without affecting the flexibility of the electrolyte when participating in the construction of the cross-linking network. A denser and more uniform network structure is formed, thereby improving the mechanical strength and ionic conductivity of the electrolyte. Furthermore, we have also introduced fluorinated acrylates with a molecular weight of 200-400g / mol. After participating in the construction of the cross-linked network, the fluorinated acrylates with a molecular weight of 200-400g / mol can help to further optimize the ion channel, balance the mechanical properties and hydrophobicity of the polymer, and improve the solvent resistance and ion selectivity of the polymer electrolyte, thereby optimizing the battery cycle stability. In addition, the polar ester groups also exist in alkyl acrylates, polyethylene glycol diacrylates and ester fluorinated acrylates, which can help to further enhance the ionic conductivity of the polymer electrolyte and improve the battery ionic conductivity. Fluorinated acrylates can also introduce fluorine elements into the electrolyte, prompting the battery to form a LiF-rich SEI film during circulation, which protects the positive and negative electrodes on the basis of further promoting the rapid transmission of lithium ions, thereby further optimizing the battery cycle performance.
[0067] As some preferred schemes, the raw materials of the high-voltage polymer electrolyte include alkyl acrylate with a molecular weight of 100-120 g / mol, polyethylene glycol diacrylate with a weight average molecular weight of 400-600 g / mol, fluorine-containing acrylate with a molecular weight of 225-350 g / mol, lithium salt, solvent, and initiator, wherein R1 is selected from methyl, R2 is selected from C1-C3 alkyl, R3 is selected from methyl, and R4 is selected from C3-C5 alkyl substituted with at least 4-12 fluorines.
[0068] Selecting alkyl acrylates with a molecular weight of 100-120 g / mol, polyethylene glycol diacrylates with a weight-average molecular weight of 400-600 g / mol, and fluorinated acrylates with a molecular weight of 225-350 g / mol for compounding can help further leverage the advantages of the three and build a denser and more uniform cross-linked network, thereby optimizing ion channels and improving the cycle performance of high-voltage polymer electrolytes. On this basis, we further optimize the structures of alkyl acrylates and fluorinated acrylates. First, when R1 and R3 are selected from methyl groups, the methyl group, as a hydrophobic group, helps to attract lithium ions. On this basis, controlling R2 to be selected from an alkyl group of C1-C3 helps to further optimize the cross-linked network, ensuring that R4 is selected from an alkyl group substituted with at least 4-12 fluorines, and the alkyl group is selected from C3-C5, can further optimize the fluorine content, thereby optimizing battery cycling and ionic conductivity.
[0069] As some exemplary schemes, the alkyl acrylate can be selected from one or more of methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, propyl acrylate, isopropyl acrylate, propyl methacrylate, butyl acrylate, isobutyl acrylate, butyl methacrylate, amyl acrylate, isoamyl acrylate, and amyl methacrylate.
[0070] As some exemplary schemes, the polyethylene glycol diacrylate can be selected from one or more polyethylene glycol diacrylates having a weight average molecular weight of 400 g / mol, 575 g / mol, 600 g / mol, 700 g / mol, and 1000 g / mol.
[0071] As some exemplary schemes, the fluorine-containing acrylates include one or more of hexafluorobutyl acrylate, 1H,1H-perfluoropropyl methacrylate, 2,2,3,3,4,4,4-heptafluoro-butyl methacrylate, 1H,1H,7H-dodecyl methacrylate, 2-(perfluorobutyl)ethyl acrylate, dodecafluoroheptyl methacrylate, octafluoropentyl acrylate, 2-(perfluorobutyl)ethyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, hexafluorobutyl methacrylate, hexafluoroisopropyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, octafluoropentyl methacrylate, pentafluorophenyl methacrylate, and hexafluorobutyl acrylate.
[0072] As a further solution, the mass content of the alkyl acrylate in the high-voltage polymer electrolyte raw material is selected from 0.1%-5%.
[0073] As a further solution, the mass content of the alkyl acrylate in the high-voltage polymer electrolyte raw material is selected from 1%-3%.
[0074] As a further solution, the mass content of the polyethylene glycol diacrylate in the high-voltage polymer electrolyte raw material is selected from 2% to 5%.
[0075] As a further solution, the mass content of the polyethylene glycol diacrylate in the high-voltage polymer electrolyte raw material is selected from 2% to 4%.
[0076] As a further solution, the mass content of the fluorine-containing acrylate in the high-voltage polymer electrolyte raw material is selected from 5% to 8%.
[0077] As a further solution, the mass content of the fluorine-containing acrylate in the high-voltage polymer electrolyte raw material is selected from 5% to 7%.
[0078] As a further solution, the mass content of the solvent in the high-voltage polymer electrolyte raw material is selected from 40% to 95%.
[0079] As a further embodiment, the solvent is selected from carbonate solvents and carboxylate solvents.
[0080] As a further solution, the carbonate solvent is selected from a mixture of one or more of cyclic carbonates and linear carbonates.
[0081] As a further embodiment, the cyclic carbonate solvent is selected from a mixture of one or more of vinylene carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, methyl vinyl carbonate, methyl propylene carbonate, fluoroethylene carbonate, fluoropropylene carbonate, bis(fluoromethyl) carbonate, difluoroethylene carbonate, vinyl carbonate, fluoroethylene carbonate, fluoroethylene carbonate, and perfluorobutyl carbonate.
[0082] As a further embodiment, the linear carbonate solvent is selected from one or a mixture of fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propyl methyl carbonate, methyl isobutyl carbonate, dipropyl carbonate, methyl propyl carbonate, dibutyl carbonate, ethyl propyl carbonate, methyl tert-butyl carbonate, and dimethyl carbonate.
[0083] As a further solution, the carboxylate solvent is selected from one or a mixture of acetate solvents, propionate solvents, and butyrate solvents.
[0084] As a further embodiment, the acetate solvent is selected from one or a mixture of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, isobutyl acetate, amyl acetate, isoamyl acetate, hexyl acetate, benzyl acetate, cyclohexyl acetate, and n-propyl acetate.
[0085] As a further embodiment, the propionate solvent is selected from one or a mixture of ethyl propionate, propyl propionate, butyl propionate, isopropyl propionate, isobutyl propionate, pentyl propionate, isopentyl propionate, hexyl propionate, ethylene glycol propionate, propylene glycol propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0086] As a further solution, the butyrate solvent is selected from one or a mixture of methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, isobutyl butyrate, and ethyl n-butyrate.
[0087] As a further solution, the high-voltage polymer electrolyte may further include a fluorine-containing co-solvent.
[0088] The interaction between the fluorinated co-solvent and the solvent can effectively weaken the coordination strength of lithium ions and solvents, promote the entry of anions into the solvation structure, and promote the formation of inorganic-rich CEI during the battery cycle, providing a more stable environment for the establishment of ion transport channels and the generation of LiF-rich SEI during battery operation, thereby optimizing and improving the battery's rate performance and cycle capacity.
[0089] As a further solution, the lithium salt is selected from any one or more of organic lithium salts and inorganic lithium salts.
[0090] As a further solution, the organic lithium salt is selected from any one or more of lithium sulfonate salts, lithium oxalate salts and lithium borate salts.
[0091] As a further embodiment, the lithium sulfonate salt is selected from any one or more of lithium trifluoromethanesulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium perfluorobutane sulfonate, lithium perfluorobutane sulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium 1,1,2,2-tetrafluoroethanesulfonate, lithium hexafluoropropanesulfonate, lithium perfluorooctanesulfonate, lithium pentafluorobenzenesulfonate, lithium 1,2,2-trifluoroethanesulfonate, and lithium octafluoropropanesulfonate.
[0092] As a further solution, the lithium borate salt is selected from any one or more of lithium difluorodihydroxyborate, lithium fluoroborate ethoxide, lithium fluoromethyleneborate, and lithium trifluoropropanolborate.
[0093] As a further solution, the inorganic lithium salt is selected from any one or more of inorganic lithium borate salts, inorganic lithium phosphate salts, and inorganic lithium chlorate salts.
[0094] As a further embodiment, the inorganic borate is selected from any one or more of lithium borohydride, lithium metaborate, lithium borate, lithium fluoroborate, lithium boron oxide, lithium tetrafluoroborate, lithium difluorooxyborate, lithium trifluoroborate, and lithium fluorophosphorus borate.
[0095] As a further solution, the inorganic lithium phosphate salt is selected from any one or more of fluorolithium phosphate, fluorolithium metaphosphate, bis(fluorooxyphosphoryl)nitrosolithium, fluorolithium phosphite, lithium trifluorophosphate, lithium hexafluorophosphate, lithium phosphate, and lithium dihydrogen phosphate.
[0096] As a further solution, the inorganic lithium chlorate salt is selected from any one or more of lithium chloride, lithium perchlorate, lithium difluorochlorate, lithium trifluorochlorate, and lithium tetrafluorochlorate.
[0097] As a further embodiment, the concentration of the lithium salt in the solvent is selected from 2-4M.
[0098] As a further scheme, the fluorine-containing co-solvent is selected from one or more of fluoroethers, fluorobenzenes, fluoroesters, and fluorosilicone ethers, wherein fluoroethers are ether compounds containing fluorine atoms replacing some or all of the hydrogen atoms, fluorobenzenes are compounds formed by one or more hydrogen atoms on the benzene ring being replaced by fluorine atoms; fluoroesters are ester compounds containing fluorine atoms replacing some or all of the hydrogen atoms; and fluorosilicone ethers are silicon ether compounds containing fluorine atoms replacing some or all of the hydrogen atoms.
[0099] As a further embodiment, the fluoroether is selected from one or more of 1,1,2,2-tetrafluorodiethyl ether, 1,1,1,3,3,3-hexafluoroisopropyl methyl ether, 1,1,2,2-tetrafluoroethyl methyl ether, 1,1,1,2,2,3,3,3-octafluoropropyl methyl ether, 1,1,2,3,3,3-hexafluoropropyl methyl ether, 1,1,1,2,2-pentafluoroethyl methyl ether, trifluoromethoxyethyl ether, 2,2,3,3-tetrafluoropropyl methyl ether, 1,1,1-trifluoroethyl methyl ether, and 1,1,1,3,3,3-hexafluoropropyl ethyl ether.
[0100] As a further embodiment, the above-mentioned is one or more selected from fluorobenzene, m-difluorobenzene, o-difluorobenzene, p-difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene and hexafluorobenzene.
[0101] As a further embodiment, the fluoroester is selected from one or more of methyl fluoroacetate, ethyl fluoroacetate, methyl trifluoroacetate, ethyl trifluoroacetate, methyl fluoromethylpropionate, ethyl fluoromethylpropionate, 2,2,2-propyl trifluoroacetate, methyl 2-fluoropropionate, methyl 2,2,3,3-tetrafluorobutyrate, and ethyl 3-fluorobutyrate.
[0102] As a further embodiment, the fluorosilyl ether is selected from one or more of methyltrifluoroethoxysilane, dimethyldifluorosilane, trifluoropropyltrimethoxysilane, ethyltrifluoroethoxysilane, diethyldifluorosilane, perfluorobutylmethylsiloxane, trifluoroethyltrifluorosilane, trifluoropropyldimethylchlorosilane, methyltrifluoropropylsilane, and perfluorohexylethylsiloxane.
[0103] As a further solution, the mass content of the fluorine-containing co-solvent in the high-voltage polymer electrolyte raw material is selected from 0 to 50%.
[0104] As a further embodiment, the initiator is selected from any one of 2,2-azobisisobutyronitrile, ammonium persulfate, azobisisobutyronitrile, benzoyl peroxide, tert-butyl peroxide, diisopropylbenzene peroxide, 2,2'-azobis(2-methylpropionitrile), dimethyl azodicarboxylate, tert-butyl hydroperoxide, and di(3,5,5-trimethylhexanoic acid) peroxide.
[0105] As a further solution, the mass of the initiator is 2% of the sum of the masses of alkyl acrylate, polyethylene glycol diacrylate and fluorine-containing acrylate.
[0106] In a second aspect, the present invention further provides a lithium ion battery, which uses the high-voltage polymer electrolyte provided by the present invention as an electrolyte.
[0107] As a further solution, the lithium-ion battery also includes a positive electrode sheet, a negative electrode sheet, and a separator.
[0108] As a further solution, the positive electrode sheet includes a positive electrode material layer and a positive electrode current collector.
[0109] As a further solution, the type of the positive electrode current collector is not limited in principle, and technicians can select the corresponding positive electrode current collector according to needs.
[0110] As a further solution, the positive electrode material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductor.
[0111] As a further solution, the positive electrode active material is selected from one of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate and a ternary material.
[0112] As a further solution, the positive electrode binder is selected from at least one of thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose and styrene butadiene rubber.
[0113] As a further embodiment, the thermoplastic resin includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, a thermoplastic polyimide, polyethylene and polypropylene.
[0114] As a further solution, the acrylic resin includes at least one of vinyl acrylate resin, methyl acrylate resin, butyl acrylate resin, acrylic styrene resin, acrylate resin, acrylate copolymer resin, acrylic resin, and acrylic emulsion resin.
[0115] As a further embodiment, the positive electrode conductor includes a crystalline carbon material and an amorphous carbon material.
[0116] As a further solution, the crystalline carbon material includes at least one of conductive graphite, carbon nanotubes, graphene, and reduced graphene oxide.
[0117] As a further solution, the amorphous carbon material includes at least one of conductive carbon black, conductive carbon balls, and conductive carbon fibers.
[0118] As a further solution, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer.
[0119] As a further solution, there is no restriction on the type of the negative electrode current collector, and technicians can select the corresponding negative electrode current collector according to their needs.
[0120] As a further solution, the negative electrode material layer includes a negative electrode active material, a negative electrode binder and a negative electrode conductor.
[0121] As a further solution, the negative electrode active material is selected from at least one of soft carbon, hard carbon, sodium titanate, metallic lithium, carbon nanotubes, carbon black, carbon aerogel, graphite, and graphene.
[0122] As a further solution, the type of the negative electrode binder is not limited, and technicians can choose it according to actual needs, including at least one of styrene butadiene rubber (SBR), styrene-butadiene rubber, water-based acrylic resin and carboxymethyl cellulose (CMC).
[0123] As a further solution, the negative electrode conductive agent is selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, conductive carbon black and carbon nanofibers.
[0124] As a further solution, the type of the diaphragm is not limited, and technicians can choose according to their needs.
[0125] In a third aspect, the present invention also provides a method for preparing a lithium-ion battery, the steps of which are as follows:
[0126] S1: uniformly mixing a lithium salt, a solvent, a fluorinated co-solvent, an alkyl acrylate, polyethylene glycol diacrylate and a fluorinated acrylate, then adding an initiator and mixing uniformly to obtain a polymer electrolyte precursor solution;
[0127] S2: Inject the polymer electrolyte precursor solution into the battery and heat and solidify it to obtain a lithium-ion battery.
[0128] As a further solution, the curing temperature in step S2 is selected from 50° C. to 80° C. The curing temperature of 50° C. to 80° C. helps to ensure the effective decomposition of the initiator, thereby promoting the efficient progress of the polymerization reaction.
[0129] As a further solution, the curing time in step S2 is selected from 7h-10h.
[0130] As a further solution, the standing time after the battery assembly is completed in step S2 is selected from 5h-8h. When the standing time is selected from 5h-8h, the solvent can fully infiltrate the electrode sheet, and the polymer can be fully polymerized, thereby optimizing the battery performance.
[0131] As some preferred solutions, the steps of preparing a lithium ion battery are as follows:
[0132] S1: mixing a lithium salt, a solvent, and a fluorinated co-solvent to obtain a solution A, and mixing an alkyl acrylate, polyethylene glycol diacrylate, and a fluorinated acrylate to obtain a solution B;
[0133] S2: Mix solution A and solution B, add initiator, mix well, and obtain a polymer electrolyte precursor solution.
[0134] S3: Inject the polymer electrolyte precursor solution into the battery and heat and solidify it to obtain a lithium-ion battery.
[0135] By mixing lithium salt, solvent, and fluorine-containing co-solvent into solution A, mixing alkyl acrylate, polyethylene glycol diacrylate and fluorine-containing acrylate into solution B, and mixing solution A and solution B, it helps to shorten the mixing time and obtain a more uniform electrolyte precursor solution to achieve more uniform curing.
[0136] As a further solution, the steps of assembling the battery are not limited in principle, and technicians can assemble it according to needs. For example, the battery can be assembled in the order of negative electrode shell, negative electrode, injection of precursor solution, separator, injection of precursor solution, positive electrode, gasket, spring clip, and positive electrode shell.
[0137] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application and do not represent all possible embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0138] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.
[0139] Example 1
[0140] S1: 3M LiTFSI and FEC / DMC / HFB (hexafluorobenzene) = 1:2:3 (Vol%) were mixed to prepare solution A, and methyl methacrylate, polyethylene glycol diacrylate, and butyl hexafluoroacrylate in a content of 2:2:6 were mixed to prepare solution B, wherein the molecular weight of methyl methacrylate was 100 g / mol, the weight average molecular weight of polyethylene glycol diacrylate was 400 g / mol, and the molecular weight of butyl hexafluoroacrylate was 300 g / mol;
[0141] S2: Mix solution A and solution B at a ratio of 90:10, add 2,2-azobisisobutyronitrile (2 wt % by weight of solution B) and mix well to obtain a polymer electrolyte precursor solution;
[0142] S3: In a glove box filled with argon, stainless steel sheets were used as positive and negative electrodes to assemble the SS||SS battery, followed by injection of the polymer electrolyte precursor solution;
[0143] Li||Al battery was assembled using metallic lithium as negative electrode and aluminum foil as positive electrode, followed by injection of polymer electrolyte precursor solution;
[0144] Using metallic lithium as positive and negative electrodes, a Li||Li symmetric battery was assembled, followed by injection of a polymer electrolyte precursor solution;
[0145] Li||LCO battery was assembled using metallic lithium as negative electrode and LCO as positive electrode, followed by injection of polymer electrolyte precursor solution;
[0146] After the injection was completed, the SS||SS battery, Li||Al battery, Li||Li symmetric battery, and Li||LCO battery were left to stand for 6 hours and then placed in an oven and cured at 60°C for 8 hours to obtain a polymer battery.
[0147] Example 2
[0148] The preparation method is the same as that of Example 1, except that butyl methacrylate is used to replace methyl methacrylate.
[0149] Example 3
[0150] The preparation method is the same as that of Example 1, except that 2,2,3,3-tetrafluoropropyl methacrylate is used to replace butyl hexafluoroacrylate.
[0151] Example 4
[0152] The preparation method is the same as that of Example 1, except that polyethylene glycol diacrylate with a weight average molecular weight of 1000 g / mol is used to replace polyethylene glycol diacrylate with a weight average molecular weight of 400 g / mol.
[0153] Example 5
[0154] The preparation method is the same as that of Example 1, except that the content of methyl methacrylate in the high-voltage polymer electrolyte raw material is 5%.
[0155] Example 6
[0156] The preparation method is the same as that of Example 1, except that the content of polyethylene glycol diacrylate in the high-voltage polymer electrolyte raw material is 5%.
[0157] Example 7
[0158] The preparation method is the same as that of Example 1, except that the content of fluorine-containing acrylate in the high-voltage polymer electrolyte raw material is 8%.
[0159] Comparative Example 1
[0160] The preparation method is the same as that of Example 1, except that methyl methacrylate is not added.
[0161] Comparative Example 2
[0162] The preparation method is the same as that of Example 1, except that polyethylene glycol diacrylate is not added.
[0163] Comparative Example 3
[0164] The preparation method is the same as that of Example 1, except that butyl hexafluoroacrylate is not added.
[0165] Comparative Example 4
[0166] The preparation method is the same as that of Example 1, except that dodecyl methacrylate is used to replace methyl methacrylate.
[0167] Comparative Example 5
[0168] The preparation method is the same as that of Example 1, except that the weight average molecular weight of polyethylene glycol diacrylate is 4000 g / mol.
[0169] Comparative Example 6
[0170] The preparation method is the same as that of Example 1, except that 4-hydroxybutyl acrylate is used to replace butyl hexafluoroacrylate.
[0171] Comparative Example 7
[0172] The preparation method is the same as in Example 1, except that hexafluorobenzene is not added.
[0173] The specific conditions of Examples 1-6 and Comparative Examples 1-7 are shown in Table 1.
[0174] Test Method
[0175] Li||Al battery electrochemical window: The electrochemical window of the electrolyte is determined by linear voltammetry (LSV). The Li||Al battery is used as the battery to be tested, and the electrochemical window is obtained by slowly scanning from the open circuit voltage of the battery to 6V at a scanning rate of 0.5mV / s.
[0176] SS||SS battery ion conductivity: Electrochemical impedance spectroscopy (EIS) was used to measure the electrolyte ion conductivity. The SS||SS battery was used as the test battery for electrochemical impedance spectroscopy, with a frequency range of 0.5-100000Hz and an amplitude of 10mV. After the test, the impedance spectroscopy results were combined with the thickness of the electrolyte (25μm) to calculate the polymer electrolyte ion conductivity.
[0177] Li||LCO cycle retention rate: Using Li||LCO battery as the test battery, the battery is charged and discharged at 3~4.6V 0.5C to explore the stability of the battery.
[0178] The Li||Li symmetrical battery was used as the battery to be tested, and the battery was subjected to constant current density charge and discharge test. The test condition was 0.5 mA / cm 2 ,0.5mAh / cm 2 Carry out a cycle;
[0179] Li||LCO battery coulombic efficiency: Li||LCO battery is the battery to be tested. The battery is charged and discharged at 3~4.6V 0.5C to explore the stability of the battery;
[0180] The electrochemical window of the electrolyte was determined by linear voltammetry (LSV). A Li||Al battery was used as the battery to be tested, and the electrochemical window was obtained by slowly scanning from the open circuit voltage of the battery to 6V at a scanning rate of 0.5mV / s.
[0181] The test results of Examples 1-7 and Comparative Examples 1-7 are shown in Table 2.
[0182] Table 1
[0183]
[0184]
[0185]
[0186]
[0187] Table 2
[0188] SS||SS battery ion conductivity (mS / cm) Li||Al battery electrochemical window (V) <![CDATA[Li||LCO cycle capacity retention rate (400 th )%]]> Example 1 0.72 5.48 84.9 Example 2 0.7 5.47 84.8 Example 3 0.71 5.4 82.6 Example 4 0.69 5.24 81.1 Example 5 0.68 5.47 84.42 Example 6 0.7 5.45 83.61 Example 7 0.69 5.46 83.74 Comparative Example 1 0.58 4.36 62.1 Comparative Example 2 0.32 3.68 0 Comparative Example 3 0.55 4.33 59.2 Comparative Example 4 0.62 4.87 72.4 Comparative Example 5 0.41 4.86 52.5 Comparative Example 6 0.57 4.54 66.2 Comparative Example 7 0.61 4.81 68.4
[0189] From Examples 1-7, Figure 1-5 It can be observed from Comparative Examples 1-7 that whether it is the ionic conductivity of the SS||SS battery, the electrochemical window of the Li||Al battery or the cycle retention rate of the Li||LCO, Examples 1-6 all show better results than Comparative Examples 1-7, indicating that when the high-voltage polymer electrolyte proposed in this scheme is used to prepare a battery, the ionic conductivity of the battery can be effectively improved, the electrochemical window of the battery can be widened, and the cycle capacity retention rate of the battery can be improved.
[0190] From Example 1 and Comparative Examples 1-3, it can be observed that in order to optimize the electrochemical performance of the battery and improve the ionic conductivity, the compounding of alkyl acrylate, polyethylene glycol diacrylate and fluorinated acrylate is very important. This may be because, on the basis of the molecular weight of alkyl acrylate being 80 g / mol to 150 g / mol, the weight average molecular weight of polyethylene glycol diacrylate being 400 g / mol to 1000 g / mol, and the molecular weight of fluorinated acrylate being 200 g / mol to 400 g / mol, polyethylene glycol diacrylate is combined to form a polymer. Among them, alkyl acrylate can build a tight and uniform network on the basis of ensuring the flexibility of the electrolyte, while the long-chain polyethylene glycol diacrylate can build ion channels and promote lithium When polyethylene glycol diacrylate is not added, the high-voltage polymer electrolyte cannot form a stable cross-linked structure. The ionic conductivity and electrochemical window of Comparative Example 2 are seriously affected, and the Li||LCO cycle retention rate is 0 after 400 cycles, indicating that polyethylene glycol diacrylate plays an important role in the high-voltage polymer electrolyte. When fluorinated acrylate is not added, the cycle performance and ionic conductivity of Comparative Example 3 are weaker than those of Comparative Example 1. This may be because the presence of fluorine in fluorinated acrylate helps to construct the SEI film containing LiF, and the presence of ester group helps to further optimize the ionic conductivity of the polymer electrolyte. When fluorinated acrylate is not added, the performance of Comparative Example 3 is significantly weaker than that of Example 1.
[0191] Example 1 and Comparative Examples 4-6 further discuss the effects of different molecular weights or weight average molecular weights on high-voltage polymer electrolytes when alkyl acrylate, polyethylene glycol diacrylate and fluorinated acrylate are compounded. First, through Example 1 and Comparative Example 4, it can be observed that when dodecyl methacrylate with a molecular weight of 254 g / mol is used to replace methyl methacrylate, Comparative Example 4 exhibits a lower ionic conductivity than Example 1, which may be because although the alkyl acrylate with a molecular weight of 254 g / mol can also cooperate with polyethylene glycol diacrylate to construct a cross-linked network, the constructed network is more sparse, thus affecting the ionic conductivity of Comparative Example 4.
[0192] As for Example 1 and Comparative Example 5, when polyethylene glycol diacrylate with a weight average molecular weight of 4000 g / mol is used, the ionic conductivity of Comparative Example 5 is only 0.41 mS / cm, the electrochemical window is only 4.86 V, and the Li||LCO cycle retention rate is only 52.5%. This may be because although the long-chain polyethylene glycol diacrylate can also form a cross-linked polymer, it cannot cooperate with alkyl acrylate and fluorine-containing acrylate to construct an efficient lithium ion channel, thereby affecting the ionic conductivity. At the same time, the electrolyte constructed with polyethylene glycol diacrylate with a weight average molecular weight of 4000 g / mol cannot fully cooperate with fluorine-containing acrylate to improve the solvent resistance of the electrolyte. Therefore, the electrochemical window and the cycle capacity retention rate are both lower than those of Example 1.
[0193] It can be observed in Example 1 and Comparative Example 6 that when 4-hydroxybutyl acrylate with a molecular weight of 144 g / mol is used to replace butyl hexafluoroacrylate, on the one hand, due to the lack of fluorine element, a LiF-rich SEI film cannot be formed in Comparative Example 6. At the same time, 4-hydroxybutyl acrylate with a molecular weight of 144 g / mol may not be able to fully cooperate with alkyl acrylate and polyethylene glycol diacrylate, resulting in the formation of an overly dense cross-linked network, affecting the transmission of ion channels. Therefore, the ionic conductivity, cycle capacity retention rate and electrochemical window of Comparative Example 6 are all affected.
[0194] Fluorinated co-solvents are also one of the factors that affect high-voltage polymer electrolytes. Compared with Example 1, the coordination strength between lithium ions and the solvent in Comparative Example 7 without adding fluorinated co-solvents is greater. At the same time, it may also affect the formation of CEI film during the cycle, resulting in alkyl acrylates, polyethylene glycol diacrylates, and fluorinated acrylates lacking a stable environment to construct lithium ion channels and SEI films, thereby affecting the performance of Comparative Example 7.
[0195] In Examples 1 and 2, we discussed the role of alkyl acrylates with different structures and different molecular weights in high-voltage polymer electrolytes. It can be observed from Example 2 that compared with butyl methacrylate as the alkyl acrylate, methyl methacrylate as the alkyl acrylate has better ionic conductivity. This may be due to two reasons. First, the molecular weight of methyl methacrylate is 100 g / mol, compared with 142 g / mol in Example 2. The molecular weight of Example 1 helps to combine polyethylene glycol diacrylate and fluorinated acrylate to build a more dense and uniform cross-linked network, thereby improving the ionic conductivity of Example 1. Second, the structure of the alkyl acrylate is also one of the factors that affect the performance of the high-voltage polymer electrolyte. Compared with Example 2, Example 1 has a shorter carbon chain, which helps to further form a dense network, so Example 1 shows better ionic conductivity than Example 2.
[0196] Examples 1 and 3 further discuss the effects of the structure and molecular weight of fluorinated acrylates on high-voltage polymer electrolytes. When butyl hexafluoroacrylate with a molecular weight of 236 g / mol is used, Example 1 exhibits a better cycle capacity retention rate than Example 3. This may be because the fluorine content of the fluorinated acrylate affects the formed interface layer, thereby affecting the electrochemical window of the electrolyte and the cycle stability of the battery.
[0197] In Examples 1 and 4, polyethylene glycol diacrylates with weight average molecular weights of 400 g / mol and 1000 g / mol were used respectively. It can be observed that the polyethylene glycol diacrylate with a weight average molecular weight of 400 g / mol exhibits better ionic conductivity and cycle capacity retention than the polyethylene glycol diacrylate with a weight average molecular weight of 1000 g / mol. At the same time, Example 1 also exhibits a higher electrochemical window. This may be because compared with Example 4, Example 1 uses polyethylene glycol diacrylate with a weight average molecular weight of 400 g / mol to construct a cross-linked network with a more appropriate degree of cross-linking, thereby constructing a denser and more stable lithium ion transmission channel during use. At the same time, polyethylene glycol diacrylate with a weight average molecular weight of 400 g / mol may also be better matched with alkyl acrylates and fluorinated acrylates, thereby optimizing the electrochemical capacity and cycle stability of Example 1.
[0198] Examples 1 and 5 further discussed the effect of the alkyl acrylate content in the high-voltage polymer electrolyte on its electrochemical properties. When the alkyl acrylate content was 2%, Example 1 exhibited better ionic conductivity and cycle capacity retention than Example 5. This may be because the amount of alkyl acrylate added in Example 1 was able to form a tight and uniform network structure when participating in the construction of a cross-linked network, while providing sufficient space for the formation of lithium ion channels and optimizing the battery cycle performance.
[0199] Examples 1 and 6 discuss the role of different polyethylene glycol diacrylate contents in the polymer electrolyte. It can be observed from Example 1 that when the added polyethylene glycol diacrylate content is 2%, Example 1 exhibits a good cycle capacity retention rate. This may be because when the polyethylene glycol diacrylate content is 2%, the formed polymer electrolyte has good flexibility and cross-linking degree, thereby optimizing the cycle performance of the polymer electrolyte.
[0200] Furthermore, we also discussed the effect of the fluorinated acrylate content on the overall performance. It can be observed from Examples 1 and 7 that, compared with Example 7 in which the fluorinated acrylate content is 8%, Example 1 exhibits better ionic conductivity, cycle capacity retention rate, and higher electrochemical window than Example 8. This may be because the fluorinated acrylate with a content of 6% can better combine with alkyl acrylate and polyethylene glycol diacrylate to construct a uniform and dense cross-linked network, improve the solvent resistance to high-voltage polymer electrolytes, thereby optimizing the cycle performance, and construct a LiF-rich SEI film, ultimately improving the battery electrochemical window.
[0201] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A high voltage polymer electrolyte, characterized in that: The precursor solution of the high-voltage polymer electrolyte includes an alkyl acrylate with a molecular weight of 80 to 150 g / mol, polyethylene glycol diacrylate with a weight average molecular weight of 400 to 1000 g / mol, a fluorine-containing acrylate with a molecular weight of 200 to 400 g / mol, a lithium salt, a solvent, and an initiator; The structural formula of alkyl acrylate is The structural formula of fluorinated acrylate is Among them, R1 and R3 are selected from one of H and methyl, R2 is selected from one of C1 to C5 alkyl groups, and R4 is selected from fluorine-substituted phenyl or C3-C7 alkyl group substituted with at least 4 fluorine groups.
2. The high-voltage polymer electrolyte according to claim 1, characterized in that: The raw materials of the high-voltage polymer electrolyte include alkyl acrylate with a molecular weight of 100 to 120 g / mol, polyethylene glycol diacrylate with a weight-average molecular weight of 400 to 600 g / mol, fluorine-containing acrylate with a molecular weight of 225 to 350 g / mol, lithium salt, solvent, and initiator, wherein R1 is selected from methyl, R2 is selected from C1 to C3 alkyl, R3 is selected from methyl, and R4 is selected from C3-C5 alkyl substituted with at least 4 to 12 fluorine atoms.
3. The high voltage polymer electrolyte according to claim 1, characterized in that: The alkyl acrylate may be selected from one or more of methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, propyl acrylate, isopropyl acrylate, propyl methacrylate, butyl acrylate, isobutyl acrylate, butyl methacrylate, amyl acrylate, isoamyl acrylate, and amyl methacrylate; Preferably, the polyethylene glycol diacrylate can be selected from one or more polyethylene glycol diacrylates having a weight average molecular weight of 400 g / mol, 575 g / mol, 600 g / mol, 700 g / mol, and 1000 g / mol; Preferably, the fluorine-containing acrylate is one or more of hexafluorobutyl acrylate, 1H,1H-perfluoropropyl methacrylate, 2,2,3,3,4,4,4-heptafluoro-butyl methacrylate, 1H,1H,7H-dodecafluoroheptyl acrylate, 2-(perfluorobutyl)ethyl acrylate, dodecafluoroheptyl methacrylate, octafluoropentyl acrylate, 2-(perfluorobutyl)ethyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, hexafluorobutyl methacrylate, hexafluoroisopropyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, octafluoropentyl methacrylate, pentafluorophenyl methacrylate, and hexafluorobutyl acrylate.
4. The high-voltage polymer electrolyte according to claim 1, characterized in that: The mass content of the alkyl acrylate in the high-voltage polymer electrolyte raw material is selected from 0.1% to 5%; Preferably, the mass content of the alkyl acrylate in the high-voltage polymer electrolyte raw material is selected from 1% to 3%; The mass content of the polyethylene glycol diacrylate in the high-voltage polymer electrolyte raw material is selected from 2% to 5%; Preferably, the mass content of the polyethylene glycol diacrylate in the high-voltage polymer electrolyte raw material is selected from 2% to 4%; The mass content of the fluorinated acrylate in the high-voltage polymer electrolyte raw material is selected from 5% to 8%; Preferably, the mass content of the fluorinated acrylate in the high-voltage polymer electrolyte raw material is selected from 5% to 7%; The mass content of the solvent in the high-voltage polymer electrolyte raw material is selected from 40% to 95%.
5. The high-voltage polymer electrolyte according to claim 1, characterized in that: The solvent is selected from carbonate solvents and carboxylate solvents; Preferably, the carbonate solvent is selected from a mixture of one or more of cyclic carbonates and linear carbonates; Preferably, the carboxylate solvent is selected from one or a mixture of acetate solvents, propionate solvents, butyrate solvents; The high-voltage polymer electrolyte also includes a fluorine-containing co-solvent; The lithium salt is selected from any one or more of organic lithium salts and inorganic lithium salts; Preferably, the organic lithium salt is selected from any one or more of lithium sulfonate salts, lithium oxalate salts and lithium borate salts; Preferably, the inorganic lithium salt is selected from any one or more of inorganic lithium borate salt, inorganic lithium phosphate salt, and inorganic lithium chlorate salt; Preferably, the concentration of the lithium salt in the solvent is selected from 2 to 4 M; Preferably, the fluorinated co-solvent is selected from one or more of fluoroethers, fluorobenzenes, fluoroesters, and fluorosilicone ethers; Preferably, the mass content of the fluorinated co-solvent in the high-voltage polymer electrolyte raw material is selected from 0 to 50%; Preferably, the mass of the initiator is 2% of the sum of the masses of alkyl acrylate, polyethylene glycol diacrylate and fluorine-containing acrylate.
6. A lithium ion battery, characterized in that: The high-voltage polymer electrolyte according to any one of claims 1 to 5 is used as the electrolyte.
7. The lithium-ion battery according to claim 6, characterized in that: The lithium-ion battery also includes a positive electrode sheet, a negative electrode sheet, and a separator; Preferably, the positive electrode sheet comprises a positive electrode material layer and a positive electrode current collector; Preferably, the positive electrode material layer comprises a positive electrode active material, a positive electrode binder and a positive electrode conductor; Preferably, the positive electrode binder is selected from at least one of thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose and styrene butadiene rubber; Preferably, the positive electrode conductive agent includes crystalline carbon material and amorphous carbon material; Preferably, the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer; Preferably, the negative electrode material layer includes a negative electrode active material, a negative electrode binder and a negative electrode conductor.
8. A method for preparing a lithium ion battery, characterized in that: The steps include: S1: uniformly mixing a lithium salt, a solvent, a fluorinated co-solvent, an alkyl acrylate, polyethylene glycol diacrylate and a fluorinated acrylate, then adding an initiator and mixing uniformly to obtain a polymer electrolyte precursor solution; S2: injecting the polymer electrolyte precursor solution into the battery and heating and curing it to obtain a lithium ion battery; Preferably, the curing temperature in step S2 is selected from 50°C to 80°C; Preferably, the curing time in step S2 is selected from 7h-10h; Preferably, the standing time after the battery assembly is completed in step S2 is selected from 5h-8h.
9. The method for preparing a lithium ion battery according to claim 8, characterized in that: The steps of preparing a lithium ion battery are as follows: S1: mixing a lithium salt, a solvent, and a fluorinated co-solvent to obtain a solution A, and mixing an alkyl acrylate, polyethylene glycol diacrylate, and a fluorinated acrylate to obtain a solution B; S2: Mix solution A and solution B, add an initiator, mix well, and obtain a polymer electrolyte precursor solution; S3: Inject the polymer electrolyte precursor solution into the battery and heat and solidify it to obtain a lithium-ion battery.
10. An energy storage device, characterized in that: A lithium-ion battery comprising the high-voltage polymer electrolyte described in any one of claims 1 to 5, the lithium-ion battery described in any one of claims 6 to 7, or a lithium-ion battery prepared by the preparation method of the lithium-ion battery described in any one of claims 8 to 9.